Sifat Ketangguhan Baja ST 42 Pasca Post Welding Heat Treatment dengan Media Pendingin Minyak Kelapa pada Variasi Holding Time - Nitha, Nitha; Tandiara, Anis; Fikran, Fikran; Bontong, Yafet; Pasae, Nofrianto; Sampelawang, Petrus (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Post-Weld Heat Treatment (PWHT) is applied in heat treatment processes, holding time, heating temperature, and cooling rate are very important factors. PWHT is also intended to relieve residual stresses (stress relieving). Therefore, this study aims to determine the effect of holding time with coconut oil as the cooling medium in PWHT on the toughness of ST 42 steel. The research method employed was an experimental method using a heat treatment temperature of 590°C, holding times of 1, 2, 3, 4, and 5 hours, and coconut oil as the cooling medium, after SMAW welding at a current of 120 A, using an E6013 electrode, flat welding position, and V-groove joint. Subsequently, toughness testing was carried out using the Charpy impact method. The steel material used in this study was ST 42. The results showed that holding time affected the toughness of PWHT-treated steel, where the lowest toughness value was 0.84 J/mm² at a holding time of 5 hours, and the highest toughness value was obtained at a holding time of 1 hour, with a toughness value of 1.366 J/mm². This proves that a longer holding time in the furnace leads to a decrease in the toughness of ST 42 steel subjected to PWHT at a temperature of 590°C.